2005
DOI: 10.1055/s-2005-869716
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of Crohn's disease: association between familial disease, smoking, disease phenotype, extraintestinal manifestations and need for surgery

Abstract: Background/Aims: Recent molecular data suggest that genetic factors may underlie the disease heterogeneity observed in Crohn's disease (CD). It was also suggested that familial inflammatory bowel disease (IBD) is a homogenous subgroup, phenotypically different from sporadic disease. Our aim was to determine the clinical presentation in a large CD population. Methodology: 564 CD patients (m/f: 278/286, age: 37.4 (SD 12.7) yrs, duration: 8.4 (7.1) yrs) were included. Disease phenotype was determined according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 39 publications
2
19
1
Order By: Relevance
“…They were more frequently seen in women than in men (41.1 vs. 26.7%), (odds ratio 1.92, 95% confidence interval: 0.99-3.70; P = 0.05) and in steroid-dependent patients than in steroid responders (61.1 vs. 28.5%), (odds ratio 3.94, 95% confidence interval: 1.83-8.49; P < 0.01). No relationship was found in general between the extraintestinal manifestations of Crohn's disease and smoking habits, previous Crohn's diseaserelated surgery, a family history of Crohn's disease, steroid resistance and CARD15 mutations.…”
mentioning
confidence: 95%
“…They were more frequently seen in women than in men (41.1 vs. 26.7%), (odds ratio 1.92, 95% confidence interval: 0.99-3.70; P = 0.05) and in steroid-dependent patients than in steroid responders (61.1 vs. 28.5%), (odds ratio 3.94, 95% confidence interval: 1.83-8.49; P < 0.01). No relationship was found in general between the extraintestinal manifestations of Crohn's disease and smoking habits, previous Crohn's diseaserelated surgery, a family history of Crohn's disease, steroid resistance and CARD15 mutations.…”
mentioning
confidence: 95%
“…However, the harmful effect of smoking on the course of CD is not a universal finding. Studies in patients from Israel and Hungary have not found differences in the need for surgery or for immunosuppressants between smokers and non-smokers [2,44,45] , and patients with only colonic involvement are less sensitive to the harmful effects of smoking [8] . Finally, the development and severity of perineal complications do not seem to be influenced by the smoking status [39] .…”
Section: Effect Of Smoking and Its Cessation On Clinical Course And Ementioning
confidence: 99%
“…A recent review [36] and previous data have demonstrated that smoking, when measured up to the time point of disease behavior classification, was associated more frequently with complicated disease, penetrating intestinal complications [34,37,38] , and greater likelihood to progress to complicated disease, as defined by development of strictures or fistulae [36] , and a higher relapse rate [2,39] . Of note, previous severity of the disease, as assessed from the therapeutics needs, was found to be similar in young patients who started smoking and in their matched controls [10] .…”
Section: Effect Of Smoking and Its Cessation On Clinical Course And Ementioning
confidence: 99%
See 1 more Smart Citation
“…Familial IBD was associated with the presence of EIMs, while ileal involvement and noninflammatory behavior independently increase the risk of surgery (24). Female gender, steroid dependency and colonic involvement are associated with the risk of developing EIMs of CD (19).…”
Section: Discussionmentioning
confidence: 98%